Can we really define the effect of psychological interventions on Quality of Life for patients with schizophrenia based on the most recent meta-analysis in the field? - Petkari, Eleni (Psychiatry Research, 2023)
[Abstract not available]
Keywords: psychological interventions; quality of life; schizophrenia; meta-analysis; Scopus(2); JCR